A Candidate Gene Study of Obstructive Sleep Apnea in European Americans and African Americans - Larkin, Emma K. (American Thoracic Society, 2010)
Rationale: Obstructive sleep apnea (OSA) is hypothesized to be influenced by genes within pathways involved with obesity, craniofacial development, inflammation, and ventilatory control. Objectives: We conducted the first candidate gene study of OSA using family data from European Americans and African Americans, selecting biologically plausible genes from within these pathways. Methods: A total of 1,080 single nucleotide polymorphisms (SNPs) were genotyped in 729 African Americans and 505 SNPs were genotyped in 694 European Americans. Coding for SNPs additively, association testing on the apnea-hypopnea index (AHI) as a continuous trait, and OSA as a dichotomous trait (AHI ≥15) was conducted using methods that account for familial correlations in models adjusted for age, age-squared, and sex, with and without body mass index. Measurements and Main Results: In European Americans, variants within C-reactive protein (CRP) and glial cell line–derived neurotrophic factor (GDNF) were associated with AHI (CRP: β = 4.6; SE = 1.1; P = 0.0000402) (GDNF: β = 4.3; SE = 1; P = 0.0000201) and with the dichotomous OSA trait (CRP: odds ratio = 2.4; 95% confidence interval, 1.5–3.9; P = 0.000170) (GDNF: odds ratio = 2; 95% confidence interval, 1.4–2.89; P = 0.0000433). In African Americans, rs9526240 within serotonin receptor 2a (HTR2A: odds ratio = 2.1; 95% confidence interval, 1.5–2.9; P = 0.00005233) was associated with OSA. Conclusions: This candidate gene analysis identified the potential role of genes operating through intermediate disease pathways to influence sleep apnea phenotypes, providing a framework for focusing future replication studies.